Analisis Penguatan Fungsi Badan Permus yawaratan Desa (BPD) di Desa Karyamukti Kabupaten Gorontalo - Napir, Suaib (Universitas Gorontalo, 2018)
The aim of this research is to investigate the function empowerment of the Village Deliberation Agency (VDA) in Karyamukti Village, Gorontalo Regency. This research is tring to investigate the function empowerment of the Village Deliberation Agency (VDA) in Karyamukti Village, Gorontalo Regency. The research method was the qualitative method with the institutional approach, and the research type was descriptive-qualitative in character. The data collections is doing by interviews, observation, and documentation. The research informants were the Chairman and the Vice-Chairman of the Village Deliberation Agency, the Village Chief, and the Community Members. The research results revealed that, First, the VDA has not been fullest accommodating and channeling the aspirations of society because VDA is using his own way system division of region and all its members are accountable to their respective territories in receiving the communitys aspirations. Second, the VDA has made the draft, discuss and instituted regulations of the village along the village chief Karyamukti, but has not shown maximum results due to a lack of human resources capabilities and less effective organization of VDA in manufacturing process of the regulation of the Karyamukti village. Third, the VDA was already conducting surveillance performance village chief Tallambalao but has not shown the maximum supervision because of the limited regulation which became guidelines for VDA and the lack of human resources capabilities of members of VDA in the surveillance.